Communities of the class Festuco-Brometea in Yelanetskyi Step Nature Reserve - Konaikova V.O. (Ukrainian Botanical Journal, 2019)
The article provides characteristics of the steppe vegetation of the class Festuco-Brometea within Yelanetskyi Step Nature Reserve. A history of geobotanical studies of this territory is briefly outlined. In total, vegetation of the class belongs to two orders, three alliances, six associations, and one variant. Communities of the alliance Festucion valesiacae in the reserve are represented by sod-cereal steppes and include one association and one variant. Communities of this alliance are formed in the areas that are exposed to anthropogenic factors; most often they are located on abandoned lands or areas under moderate grazing on the planes. Communities of the alliance Stipion lessingianae grow on black soils (chernozem) but with some inclusion of limestone. This alliance includes three associations which occupy ravine slopes of various steepness and exposure. The alliance Potentillo arenarie-Linion czerniaevii is represented by the communities on the limestone outcrops. It was established that the last two alliances demonstrate higher floristic diversity, which can be explained by differentiation of syntaxa within the area. The communities of these alliances include species from the European Red List and the IUCN Red List. Species listed in the Red Data Book of Ukraine are present in all syntaxa. A number of threats for the steppe communities on the study area have been identified.